Editorial: liver disease in secondary care—'money or your life'. Authors' reply. Issue 6 (23rd August 2021) - Roberts, Surain B.; Verma, Amol A.; Hirschfield, Gideon M.
LINKED CONTENT: This article is linked to Roberts et al and Trivedi papers. To view these articles, visit https://doi.org/10.1111/apt.16488 and https://doi.org/10.1111/apt.16540